2006
DOI: 10.1080/07357900600817758
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival in Metastatic Melanoma Patients Treated with Sequential Biochemotherapy: Report of a Phase II Study

Abstract: The overall survival for patients with metastatic melanoma is very poor, with a median survival of 8.5 months. In this Phase II trial, we assessed the efficacy, safety, and tolerability of a sequential biochemotherapy schedule, using dacarbazine as antiblastic agent and immunomodulant doses of interleukin-2 and interferon-alfa. Thirty-one eligible patients with metastatic melanoma received dacarbazine IV as antiblastic therapy and interluekin-2, plus interferon-alfa SC as sequential immunotherapy, for 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…23,24 Many melanoma vaccines are designed to use dendritic cells to present antigen and initiate the T-cell response through both naïve and memory CD8 1 and CD4 1 T lymphocytes. Attempts to use interleukin 2 to stimulate an immune response have shown some promise, 25 and other studies have shown that patients with advanced cancer produce less T H 1 cytokines in response to stimulation than do healthy control subjects. 6 Immunosuppressive medications used in solid organ transplant recipients have a primary focus of inhibiting T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Many melanoma vaccines are designed to use dendritic cells to present antigen and initiate the T-cell response through both naïve and memory CD8 1 and CD4 1 T lymphocytes. Attempts to use interleukin 2 to stimulate an immune response have shown some promise, 25 and other studies have shown that patients with advanced cancer produce less T H 1 cytokines in response to stimulation than do healthy control subjects. 6 Immunosuppressive medications used in solid organ transplant recipients have a primary focus of inhibiting T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of metastatic MM transmitted with the donated organs leading to high mortality in the recipients [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] have been reported. Penn 33 recorded data of 13 donors with MM who provided organs to 28 recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to metastasize in combination with resistance to conventional anticancer chemotherapy makes melanoma extremely difficult to cure, and the median survival of patients with metastatic melanoma is 8.5 months. [1][2][3] A better understanding of the biology behind melanoma aggressiveness is imperative to facilitate the development of novel anti-melanoma strategies.…”
mentioning
confidence: 99%